Map of India, and Birmah (James Wyld, 1870)
Informacje o: "Course of the Monsoons, Overland Route to India. Distances".
by James Wyld, geographer to the Queen, Charing Cross East, and model of the Earth, Leicester Square, London ; [W. J. Golbourn].
Keywords: Mapy administracyjne; Birma; Kartografia; Indie; w kartografii